Metastatic Osseous Pain Control: Bone Ablation and Cementoplasty - Kelekis, Alexis; Cornelis, Francois H.; Tutton, Sean; Filippiadis, Dimitrios (Seminars in Interventional Radiology, 2017)
Nociceptive and/or neuropathic pain can be present in all phases of cancer (early and metastatic) and are not adequately treated in 56 to 82.3% of patients. In these patients, radiotherapy achieves overall pain responses (complete and partial responses combined) up to 60 and 61%. On the other hand, nowadays, ablation is included in clinical guidelines for bone metastases and the technique is governed by level I evidence. Depending on the location of the lesion in the peripheral skeleton, either the Mirels scoring or the Harrington (alternatively the Levy) grading system can be used for prophylactic fixation recommendation. As minimally invasive treatment options may be considered in patients with poor clinical status or limited life expectancy, the aim of this review is to detail the techniques proposed so far in the literature and to report the results in terms of safety and efficacy of ablation and cementoplasty (with or without fixation) for bone metastases. Percutaneous image-guided treatments appear as an interesting alternative for localized metastatic lesions of the peripheral skeleton.
Keywords: ablation; cementoplasty; pain; bone metastasis; interventional radiology